Income distribution and the multiplier: An exploration of nonlinear distribution effects in linear Kaleckian distribution and growth models - Franz J. Prante (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
In this paper, I show that the income-autonomous demand multiplier of Keynesian-Kaleckian models is endogenous to changes in income distribution. This effect gives rise to non-linearity of distributional effects, even in basic models. Under certain conditions, an important consequence from the distribution-sensitive multiplier is that a higher wage share can have increasingly expansionary effects, which might even shift a profit-led investment regime to a wage-led one in the basic post-Kaleckian model. Surprisingly, the respective literature on distribution and growth largely ignored these features of Keynesian-Kaleckian macroeconomic models. After a theoretical discussion on the implications of the distribution-sensitive multiplier in basic closed- and openeconomy models, I present a counterfactual illustration based on empirical parameter estimations from the literature and the development of functional income distribution for selected EU countries. My analysis indicates that a rising profit share has put partial downward pressure on the wage-ledness of aggregate demand in many EU countries. These results stress the relevance of this particular form of path dependency for empirical research and policy debates on distribution and growth.
Keywords: D31; D33; E11; E12; F41; 330; Keynesian models; Kaleckian models; Multiplier; Income distribution; Open economy